Electric and hydrogen buses: Shifting from conventionally fuelled cars in the UK. (August 2020) - Logan, Kathryn G.; Nelson, John D.; Hastings, Astley
Highlights: At full capacity, bus emissions were 1.8 times lower than cars per person. Vehicle technology improvements cannot solely be relied upon to reduce emissions. Decarbonisation of electricity is needed to reduce electric and hydrogen emissions. Electric buses produce lower levels of cumulative emissions than hydrogen buses. Integrating electric buses will help to support the UK's emission targets. Abstract: For the UK to meet their national target of net zero emissions as part of the central Paris Agreement target, further emphasis needs to be placed on decarbonizing public transport and moving away from personal transport (conventionally fuelled vehicles (CFVs) and electric vehicles (EVs)). Electric buses (EBs) and hydrogen buses (HBs) have the potential to fulfil requirements if powered from low carbon renewable energy sources. A comparison of carbon dioxide (CO2 ) emissions produced from conventionally fuelled buses (CFB), EBs and HBs between 2017 and 2050 under four National Grid electricity scenarios was conducted. In addition, emissions per person at different vehicle capacity levels (100%, 75%, 50% and 25%) were projected for CFBs, HBs, EBs and personal transport assuming a maximum of 80 passengers per bus and four per personal vehicle. Results indicated that CFVs produced 30 gCO2 km −1 per person compared to 16.3 gCO2 km −1 per person by CFBs by 2050. At 100% capacity, under the two-degree scenario, CFB emissions were 36 times higher than EBs, 9 times higher than HBs and 12 times higher than EVs in 2050. Cumulative emissions under all electricity scenarios remained lower for EBs and HBs. Policy makers need to focus on encouraging a modal shift from personal transport towards sustainable public transport, primarily EBs as the lowest level emitting vehicle type. Simple electrification of personal vehicles will not meet the required targets. Simultaneously, CFBs need to be replaced with EBs and HBs if the UK is going to meet emission targets.